2012
DOI: 10.1105/tpc.112.105023
|View full text |Cite
|
Sign up to set email alerts
|

A Triantagonistic Basic Helix-Loop-Helix System Regulates Cell Elongation in Arabidopsis

Abstract: In plants, basic helix-loop-helix (bHLH) transcription factors play important roles in the control of cell elongation. Two bHLH proteins, PACLOBTRAZOL RESISTANCE1 (PRE1) and Arabidopsis ILI1 binding bHLH1 (IBH1), antagonistically regulate cell elongation in response to brassinosteroid and gibberellin signaling, but the detailed molecular mechanisms by which these factors regulate cell elongation remain unclear. Here, we identify the bHLH transcriptional activators for cell elongation (ACEs) and demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
161
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(167 citation statements)
references
References 43 publications
6
161
0
Order By: Relevance
“…The expression of a small group of genes peaked at 45 min ( Figure 6C, purple cluster). Notably, this group includes the gene ILI1 BINDING BHLH1, encoding a small HLH protein that was previously shown to regulate hypocotyl elongation (Bai et al, 2012;Ikeda et al, 2012). Among the genes whose expression peaked at 90 min ( Figure 6C, blue cluster), several terms associated with hormone pathways were enriched (Supplemental Data Set 8).…”
Section: Shade Treatment Leads To a Strong Genomic Signature Of Enhanmentioning
confidence: 95%
“…The expression of a small group of genes peaked at 45 min ( Figure 6C, purple cluster). Notably, this group includes the gene ILI1 BINDING BHLH1, encoding a small HLH protein that was previously shown to regulate hypocotyl elongation (Bai et al, 2012;Ikeda et al, 2012). Among the genes whose expression peaked at 90 min ( Figure 6C, blue cluster), several terms associated with hormone pathways were enriched (Supplemental Data Set 8).…”
Section: Shade Treatment Leads To a Strong Genomic Signature Of Enhanmentioning
confidence: 95%
“…However, overexpression of BEE1 enhanced BR response only in root but caused no obvious hypocotyl phenotype. Yeast two-hybrid assays showed that IBH1 interacts with not only HBI1 but also BEE2 and seven additional homologous bHLHs (see Supplemental Figure 2 online; Ikeda et al, 2012). BEE2 and these other bHLH factors may play redundant roles with HBI1, and BR may regulate their activities at transcriptional and/or posttranslational levels.…”
Section: Discussionmentioning
confidence: 99%
“…HBI1, ACE1, ACE2, ACE3, and CIB1 positively regulate cell elongation downstream of BRs, GAs, temperature, and light signaling. ACE1 and HBI1 activate directly elongation-promoting genes, such as EXPANSIN and XYLOGLUCAN ENDOTRANSGLYCOSYLASE/HYDROLASE (5,6). Whereas IBH1 interacts with HBI1 and ACE1 to inhibit their binding to DNA, PRE1 binds to IBH1 to prevent its repressive effect on HBI1 or ACE1, thus activating it.…”
mentioning
confidence: 99%
“…This regulatory mechanism involves activation of members of the PACLOBUTRAZOL RESISTANCE (PRE) family of atypical basic helix-loop-helix (bHLH) transcription factors (1)(2)(3)(4)(5)(6). PRE members are helix-loop-helix (HLH) proteins that lack the basic domain required for DNA binding and antagonize their interacting HLH or bHLH proteins, of which most act as cell elongation suppressors, thus forming triantagonistic bHLH systems (5,6). An example of such a system is the Arabidopsis thaliana PRE1 and its interactor, the HLH factor INCREASED LEAF INCLINATION1 BINDING bHLH1 (IBH1).…”
mentioning
confidence: 99%
See 1 more Smart Citation